The Impact of Female Leadership in HRM on Employee Wellbeing and Organizational Culture - Tulyaganova Aziza (Scientific Trends, 2025)
This article examines the influence of female leadership in Human Resource Management (HRM) on employee wellbeing and organizational culture. Women’s increasing participation in HR leadership is reshaping workplace policies, communication, and engagement strategies. The study employs a mixed-method approach combining survey data, interviews, and statistical analysis to determine the correlation between female HR leadership and improved employee outcomes. Findings demonstrate that female-led HR departments implement more inclusive, empathetic, and sustainable wellbeing initiatives, which foster healthier organizational cultures. The study contributes to the ongoing discourse on gender and leadership in modern workplaces
Keywords: Female leadership, HRM, organizational culture, wellbeing, diversity, inclusion, workplace engagement.